Predictors of Health-Related Quality of Life in Adult HemophiliaPatients in Cipto Mangunkusumo Hospital - Prasetyawaty, Findy; Sukrisman, Lugyanti; Setyohadi, Bambang (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Currently, one of the main focus of hemophilia treatment is to increase health-related quality of life. Due to financial constraints, factor VIII substitution is used only on demand in Indonesia, which might contribute to musculoskeletal complications and affect the quality of life of adult hemophilia patients. This study aimed to evaluate quality of life of adult hemophilic patients and its related factors. Methods. A cross-sectional study on hemophilia patients aged 18 years or older was conducted at the Hematology-Medical Oncology outpatient clinic, Cipto Mangunkusumo Hospital Jakarta from March to May 2012. The radiologic assessment for arthropathy used the Arnold-Hilgartner score and health-related quality of life was assessed by the SF-36 questionnaire, using norm-based scoring system with normal value of 45 (individual) and 47 (group scale score). Subjects were categorized based on the level of factor VIII or IX and clinical severity (the number of bleeding episodes during the last 12 months). Results. In 66 subjects aged 18-57 (median 28) years old, the scores of the SF-36 ranged from 42.1 (role physical) to 60.9 (vitality). The physical and mental component summary scored 40.0 and 57.7. Clinical severity (p=0.001) and the severity of arthropathy (p=0.034) significantly influenced the SF-36 scores. The multivariate analysis showed that clinical severity significantly influenced the SF-36 scores (p=0.004; AUC 73%). The combination of clinical severity and severity of arthropaty increased the AUC to 76.6%. Conclusions. Health-related quality of life in adult hemophilia showed poor results in physical components. The clinical severity and arthropathy were predictors of health-related quality of life in adult hemophilic patients. The combination of clinical severity and arthropathy had better value in predicting health-related quality of life in adult hemophilia.